2024
DOI: 10.3390/nu16071017
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Diversity of Coenzyme Q10 Intake from Dietary Sources and the Risk of New-Onset Hypertension: A Nationwide Cohort Study

Suming Dai,
Zezhong Tian,
Dan Zhao
et al.

Abstract: Coenzyme Q10 (CoQ10) is a food active component with blood-pressure-improving properties. However, the association between the variety and quantity of different sources of dietary CoQ10 and new-onset hypertension remains uncertain. We aimed to investigate the associations between the diversity and quantity of CoQ10 intake from eight major food sources and new-onset hypertension risk. A total of 11,489 participants were included. Dietary intake was evaluated via three consecutive 24 h recalls and household food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Nevertheless, we controlled for numerous confounding factors to minimize their potential impact. These findings are consistent with our recent cohort study, which demonstrated a negative association between moderate CoQ10 intake from diverse dietary sources and the incidence of new-onset hypertension [27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nevertheless, we controlled for numerous confounding factors to minimize their potential impact. These findings are consistent with our recent cohort study, which demonstrated a negative association between moderate CoQ10 intake from diverse dietary sources and the incidence of new-onset hypertension [27].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, an intervention study on Mediterranean diets demonstrated a significant reduction in systolic blood pressure (−5.5 mm Hg; 95% CI, −10.7 to −0.4), which may be attributed to its antioxidant-rich components from fruits, vegetables, and olive oil [35,36]. Furthermore, it was reported that dietary diversity has been associated with improved blood pressure, especially with some healthier rich-CoQ10 choices [27]. Our study indicated that increased CoQ10 intake from dietary sources also means a higher intake of other nutrients (such as fats, potentially posing health risks) [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these findings are limited, prompting the need for further research and evaluation of the necessity for additional CoQ10 intake beyond the standard diet. Products that can be considered cardiometabolic-protective due to their CoQ10 content include, among others, wheat germ, fatty fish, oils, and nuts [ 33 ]. It is worth bearing in mind that in addition to CoQ10, these products contain multiple other components, such as vitamin E, plant sterols, and unsaturated fatty acids, the supply of which brings health benefits.…”
Section: Food Compounds In Cardiometabolic Preventionmentioning
confidence: 99%